3539 Relationship between dental fluorosis, water and serum levels of fluoride and chronic kidney disease in children: Data from National Health and Nutrition Examination Survey. (27th March 2019) - Shaheen, Magda; Sadeghi, Erfun; Teklehaimanot, Senait
Abstract : OBJECTIVES/SPECIFIC AIMS: The aim of the study is to examine the relation between dental fluorosis, serum and water levels of fluoride and Chronic Kidney Disease (CKD) among children. A link between dental fluorosis, fluoride level and CKD can be an indicator of the blind danger of fluoride toxicity that poses a great threat to the human health. METHODS/STUDY POPULATION: Dental fluorosis, serum and water levels of fluoride and CKD were examined in children 6-19 years old, using data from the National Health and Nutrition Examination Survey1999-2012 and 2013-2016. We used multiple logistic regression to adjust for the confounders (demographics, insurance, dental visit, and co-morbidity) to assess the relation between dental fluorosis, serum and water levels of fluoride and CKD. STATA 14.0 was used to analyze the data (sample design and weight). P < 0.05 is statistically significant. RESULTS/ANTICIPATED RESULTS: The prevalence of CKD was 13.9% and dental fluorosis was 34.3%. In the multivariate model, plasma fluoride level was independently associated with CKD (Adjusted Odds Ratio (AOR) = 1.68, 95% Confidence Interval (CI) = 1.06-2.68, p = 0.029) but not with dental fluorosis (AOR = 1.4, 95% CI = 0.87-2.2, p = 0.17) or water fluoride level (AOR = 0.91, 95% CI = 0.59-1.396, p = 0.659). DISCUSSION/SIGNIFICANCE OF IMPACT: Results indicated that serum fluoride level is independently associated with CKD but dental fluorosis and water fluoride level were not related to CKD. Increase awareness and screening for fluorosis in children are needed for early detection and prevention of organ damage. Prospective studies related to fluorosis and tissue damage are needed.